Implementation of the Flutter Framework for Developing an E-Commerce Application - Nursobah Nursobah; Muhammad Ibnu Saad; Joese Andrew Josly Kansil (Politeknik Pertanian Negeri Samarinda, 2024)
The use of digital technology in the retail business has become imperative for competing in the modern era. For businesses such as vegetable shops, the presence of a digital platform is no longer an option but a critical necessity to remain relevant and competitive in an increasingly challenging market. Garvita Fresh Vegetable Shop still relies on conventional methods for vegetable ordering, typically conducted through platforms like Instagram or WhatsApp. In this context, there is a significant opportunity to enhance efficiency and customer experience by introducing a dedicated and well-integrated e-commerce platform. Therefore, the development of an e-commerce application using the Flutter framework for Garvita Fresh is essential. This application is developed using Visual Studio Code, the Flutter framework, and Firebase as the database. Data collection methods include observation, and the system development employs the waterfall model due to its clear, practical, and well-defined stages. System testing includes Black Box and Beta Testing, ensuring that the resulting application meets the expectations of prospective users.